Assessment of heart rates and blood pressure in different Salat positions - Doufesh, H.; Ibrahim, F.; Ismail, N.A.; Wan Ahmad, W.A. (2013)
Purpose This study reports the effects of the Muslim prayer, known as Salat, on heart rate (HR) and blood pressure (BP) while performing and miming the actions of Salat: standing, bowing, prostrating and sitting. Subjects Thirty Muslim subjects were asked to perform the actual and mime Salat. Methods HR and BP were measured using a Schiller AT-102 Electrocardiograph and an Omron SEM-1 Automatic Blood Pressure Monitor. Results The findings revealed that there was a significant difference in the HR of the subjects between performing and miming Salat. The standing and prostration positions of Salat produced the highest and the lowest HR, respectively. A lower HR may be of potential benefit to an individual's health. The systolic and the diastolic BP decreased significantly after performance and mime of Salat, and a greater reduction in BP was observed during performance of Salat. Conclusion This is the first study of HR and BP in relation to Salat positions. The findings will encourage further studies to explore the benefits of Salat maneuvers for patients with cardiovascular diseases.